The effect of sexual health literacy on sexual function mediated by sexual satisfaction and sexual self-efficacy: Structural equation modeling approach - Mojdeh Banaei; Saeed Hosseini; Shiva Alizadeh; Nasibeh Roozbeh; Behnaz Jahanshahloo; Elham Ghasemi; Vida Ghasemi (PLoS ONE, 2025)
Existing literature suggests that sexual health literacy may influence sexual function by enhancing sexual satisfaction and other dimensions of sexual health. This study aimed to investigate the effect of sexual health literacy on sexual function, mediated by sexual satisfaction and sexual self-efficacy, among Iranian women. A cross-sectional study was conducted using structural equation modeling (SEM) with 431 eligible women of childbearing age recruited from health centers in Asadabad city, Hamadan, Iran, from 2023 to 2024 through convenience sampling method. Data were collected using several tools: demographic and obstetric information form, sexual health literacy for adults (SHELA) questionnaire, female sexual function index (FSFI), sexual self-efficacy questionnaire (SSE), and the inventory of sexual satisfaction (ISS). Structural equation modeling was performed using IBM SPSS AMOS version 23. The mean ± SD age of the participants was 31.92 ± 7.24 years. The direct effects of sexual health literacy, sexual self-efficacy, and sexual satisfaction on sexual function were significant (P < 0.001). The indirect effect of sexual health literacy on sexual function, mediated by sexual satisfaction, was also significant (P < 0.001). Overall, the total effect (direct and indirect) of sexual health literacy on sexual function was deemed appropriate, and the proposed conceptual model demonstrated a good fit with the data (χ2/df = 3.35; CFI = 0.966; IFI = 0.967; GFI = 0.951; AGFI = 0.904; RMSEA = 0.070). Based on these findings, sexual health literacy has both direct and indirect effects (mediated by sexual satisfaction) on sexual function. These results may guide professionals in the field of marital relationships to recognize the importance of sexual health literacy and to develop educational or counseling interventions aimed at improving sexual health literacy, ultimately enhancing sexual function.